2016
DOI: 10.1007/s10068-016-0079-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of mung bean (Vigna radiata L.) seed and sprout extracts on melanogenesis

Abstract: Inhibitory effect against melanogenesis and the tyrosinase inhibitory activity of ethyl acetate (EtOAc) and methylene chloride fractions of 80% methanol extracts of mung bean ( L.) seeds and sprouts were determined. EtOAc extract fractions from mung bean sprouts germinated for 12 h (33.5%), 1 day (56.5%), and 2 days (47.9%) inhibited melanogenesis more effectively than arbutin (16.3%). The tyrosinase inhibitory activity was higher in an EtOAc extract fraction from mung bean sprouts germinated for 2 days (70.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In this study, two pure compounds separated from the ethyl acetate extract fraction were identified as vitexin and isovitexin. In another study, an ethyl acetate extract of mung bean seeds and its sprouts was also investigated for inhibitory effects against melanogenesis using B16F1 melanoma cells [79]. The results showed that inhibitory effects against melanogenesis were especially apparent for 10 μg/mL ethyl acetate fractions of mung bean sprouts (germinated for 1 day), with values of 56.5% in B16F1 melanoma cells treated with a 200 nM α-melanocyte-stimulating hormone.…”
Section: Health Benefitsmentioning
confidence: 99%
“…In this study, two pure compounds separated from the ethyl acetate extract fraction were identified as vitexin and isovitexin. In another study, an ethyl acetate extract of mung bean seeds and its sprouts was also investigated for inhibitory effects against melanogenesis using B16F1 melanoma cells [79]. The results showed that inhibitory effects against melanogenesis were especially apparent for 10 μg/mL ethyl acetate fractions of mung bean sprouts (germinated for 1 day), with values of 56.5% in B16F1 melanoma cells treated with a 200 nM α-melanocyte-stimulating hormone.…”
Section: Health Benefitsmentioning
confidence: 99%
“…The tyrosinase inhibition was first reported in Vigna mungo (Zia-Ul-Haq 2014). The increase in the tyrosinase inhibition was also reported in Vigna radiata upon sprouting (Jeong 2016). Yao et al (2011) studied the tyrosinase inhibition activity in 16 legumes and found maximum tyrosinase inhibition activity in mung bean with inhibition percentage of 81.24%.…”
Section: Resultsmentioning
confidence: 62%
“…Across the world, many cosmetic companies have tried to create products that include a cosmeceutical ingredient to address these aging factors. 46–48 However, the aging process can vary because of the exposome (external and lifestyle factors). 1 , 9 , 10 , 49 Although skin health and aging are affected by both the genome and exposome, an individual’s intrinsic genes do not change.…”
Section: Discussionmentioning
confidence: 99%